A radio structure resolved at the deca-parsec scale in the radio-quiet quasar PDS 456 with an extremely powerful X-ray outflow. Issue 2 (3rd November 2018) - Yang, Jun; An, Tao; Zheng, Fang; Baan, Willem A; Paragi, Zsolt; Mohan, Prashanth; Zhang, Zhongli; Liu, Xiang
Abstract: Active galactic nuclei (AGNs) accreting at rates close to the Eddington limit can host radiatively driven mildly relativistic outflows. Some of these X-ray absorbing but powerful outflows can produce strong shocks, resulting in a significant non-thermal emission. This outflow-driven radio emission might be detectable in the radio-quiet quasar PDS 456, as it has a bolometric luminosity that reaches the Eddington limit and a relativistic wide-aperture X-ray outflow with a kinetic power high enough to quench the star formation in its host galaxy. To investigate this possibility, we performed very-long-baseline interferometric (VLBI) observations of the quasar with the European VLBI Network (EVN) at 5 GHz. The full-resolution EVN image reveals two faint and diffuse radio components with a projected separation of about 20 pc and an average brightness temperature of around two million Kelvin. In relation to the optical submas-accuracy position measured by the Gaia mission, the two components are very likely on opposite sides of an undetected radio core. Thus, the VLBI structure at the deca-pc scale could be either a young jet or a bidirectional radio-emitting outflow, launched in the vicinity of a strongly accreting central engine. Two diffuse components at the hecto-pc scale, likely the relic radio emission from past AGN activity, are tentatively detected on each side in the low-resolution EVN image.